Working like a mule? The physiological toll of heavy loads on mules - Tadich, Tamara; Calderón-Amor, Javiera; González, Igor; Palma, Bárbara; Lagos, Javiera (Frontiers in Veterinary Science, 2025)
BackgroundWorking mules are essential for human livelihoods, yet scientific evidence on their physiological limits during load-carrying tasks remains scarce.ObjectivesTo evaluate the physiological responses of mules to increasing loads during short-distance work.Study designA crossover design. For this, 12 Chilean Army mules of three sizes (small, medium, large) were subjected to a 2-km walk carrying loads of 0, 80, 105, and 130 kg, equivalent to 20–42% of live body weight, under ambient temperatures of 32–39 °C. Blood and physiological parameters were measured before, immediately after, 10 min, and 2 h after work, with additional blood samples for biochemical parameters collected up to 105 h after exercise. Linear mixed models were applied to evaluate the effects of load, time, and body size.ResultsThe size of the mule did not have an effect on their physiological response to work. On the other hand, increasing load significantly elevated cortisol, lactate, and rectal temperature, indicating activation of both the hypothalamic–pituitary–adrenal axis and anaerobic metabolism. Enzymatic activities of γ-glutamyltransferase (GGT), lactate dehydrogenase (LDH), and alkaline phosphatase (SAP/ALP) also increased with heavier loads, suggesting greater muscular effort and mild tissue stress. Conversely, glutathione peroxidase (GPx) activity decreased as load increased, implying increased oxidative demand. Total protein and neutrophil-to-lymphocyte ratios rose with higher loads, reflecting systemic stress response and hemoconcentration. Heart rate and respiratory rate were not significantly affected, suggesting adequate cardiovascular adaptation. Most parameters returned to baseline within 2 h post-exercise, demonstrating effective short-term recovery.ConclusionThese findings confirm that short-distance work carrying heavy loads, in particular over 105 kg, does activate a physiological stress response in mules, though within adaptive limits. Loads of 105–130 kg triggered greater metabolic and enzymatic adjustments, indicating that while trained mules can cope with high loads over short distances, care should be taken when asking mules to work for longer distances or heavier loads since it can negatively affect their welfare. Establishing evidence-based workload thresholds is essential for balancing performance efficiency and welfare in working mules. Future studies should evaluate long-term work under field conditions, incorporating other welfare indicators such as behavior for a more comprehensive welfare assessment.